2018
DOI: 10.3389/fphar.2018.01379
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Selective JAK2 Inhibitor Identified Using Pharmacological Interactions

Abstract: The JAK2/STAT signaling pathway mediates cytokine receptor signals that are involved in cell growth, survival and homeostasis. JAK2 is a member of the Janus kinase (JAK) family and aberrant JAK2/STAT is involved with various diseases, making the pathway a therapeutic target. The similarity between the ATP binding site of protein kinases has made development of specific inhibitors difficult. Current JAK2 inhibitors are not selective and produce unwanted side effects. It is thought that increasing selectivity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 60 publications
1
30
0
Order By: Relevance
“…In this study, this aberration was observed in six patients including two normal-like TN and three basal-like TN tumours highlighting the genomic similarities between triple-negative molecular phenotypes across FMCs and HBCs. Tumours carrying this mutation are characterised by the co-gain of PD-L1, PD-L2, and JAK2, and might benefit from immune checkpoint targeted therapies 57,78,79 or adjuvant therapy with JAK2-specific inhibitors 80,81 . Interestingly, the Jak-STAT signalling pathway was the only KEGG pathway enriched with amplified genes in the basal-like TN subtype.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, this aberration was observed in six patients including two normal-like TN and three basal-like TN tumours highlighting the genomic similarities between triple-negative molecular phenotypes across FMCs and HBCs. Tumours carrying this mutation are characterised by the co-gain of PD-L1, PD-L2, and JAK2, and might benefit from immune checkpoint targeted therapies 57,78,79 or adjuvant therapy with JAK2-specific inhibitors 80,81 . Interestingly, the Jak-STAT signalling pathway was the only KEGG pathway enriched with amplified genes in the basal-like TN subtype.…”
Section: Discussionmentioning
confidence: 99%
“…The docking pose of the 30 known BTK inhibitors was analysed to identify possible binding interactions. This study recognises a binding interaction if a residue was observed to form an interaction with ≥ 50% of the BTK inhibitors 17 . The calculation for binding interactions is as follows: where the binding interaction score, S ( i ), for a compound, i , equals the number of binding interactions the compound forms, N ( i ), plus the docking score , D ( i ), of a compound i generated using LeadIT.…”
Section: Methodsmentioning
confidence: 87%
“…For our study, a binding interaction was considered if ≥ 50% of the 30 diverse BTK inhibitors formed an interaction with a binding site residue 17 . As a result, two hydrogen-bonding and four hydrophobic interactions were identified ( Figure 1(A,B) ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations